2019
DOI: 10.1097/sap.0000000000001598
|View full text |Cite
|
Sign up to set email alerts
|

Time to Radiation After Oncoplastic Reduction

Abstract: Background Partial breast reconstruction with reduction mammaplasty is an accepted option for women with breast cancer who wish to receive breast conserving therapy. With additional surgery and potential postoperative complications, the impact this approach has on the timely initiation of adjuvant radiation therapy has been raised as a concern. The purpose of this study was to determine if any postoperative complications after oncoplastic reduction (OCR) are associated with a delay in time to radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 20 publications
1
43
1
Order By: Relevance
“…However, a more recent study from the same group reported their institutional experience with 118 cases of oncoplastic reduction, of which 22% experienced complications including cellulitis, delayed healing, seroma, and dehiscence. The median time to radiation was significantly higher amongst patients who had complications (74 versus 54 days, P<0.001) (44).…”
Section: Complications and Delay Of Adjuvant Therapymentioning
confidence: 89%
“…However, a more recent study from the same group reported their institutional experience with 118 cases of oncoplastic reduction, of which 22% experienced complications including cellulitis, delayed healing, seroma, and dehiscence. The median time to radiation was significantly higher amongst patients who had complications (74 versus 54 days, P<0.001) (44).…”
Section: Complications and Delay Of Adjuvant Therapymentioning
confidence: 89%
“…We also found no significant difference in delays to adjuvant radiotherapy. Any potential differences in incidence of IBTR could not be estimated due to the relatively short follow-up times and very few IBTR events, which were limitations also noted in previous studies [8,11,14,15,17,18]. Finally, we evaluated the relationship between the ratio of the CTV volume to tumor size and reception of BRT.…”
Section: Discussionmentioning
confidence: 99%
“…We also found no signi cant difference in delays to adjuvant radiotherapy. Any potential differences in incidence of IBTR could not be estimated due to the relatively short follow-up times and very few IBTR events, which were limitations also noted in previous studies [8,11,14,15,17,18]. Finally, we evaluated the relationship between the ratio of post-operative seroma volume to tumor size and reception of BRT.…”
Section: Discussionmentioning
confidence: 99%